LIFE OF REASON. - SANTAYANA, GEORGE (OPEN ROAD MEDIA, 2017)
George Santayana's renowned work of moral philosophy outlines his vision of the ideal life. Those who cannot remember the past are condemned to repeat it. George Santayana's The Life of Reason stands as one of the most influential and beautifully written works of philosophical naturalism. In it, Santayana articulates his vision of human progression from chaos to reason and the pursuit of the ideal life. Focusing his thought on the lived experiences of people, these phases are traced through humanity's many endeavors, including art, science, politics, religion, friendship, and reason. Drawing on a range of influences, from Democritus and Aristotle to Spinoza and Schopenhauer, Santayana develops a materialist system of thought that stresses the importance of imagination and spiritual experience. Originally published in five volumes, from 1905 to 1906, The Life of Reason is Santayana's most complete statement of moral philosophy and an inspiring account of human dignity. This ebook has been professionally proofread to ensure accuracy and readability on all devices.